Evaluation of non-HDL-c and total cholesterol: HDL-c Ratio as Cumulative Marker of Cardiovascular Risk in Diabetes Mellitus - Aryal, M; Poudel, A; Satyal, B; Gyawali, P; Pokheral, B R; Raut, B K; Adhikari, R K; Koju, R (Kathmandu University Medical Journal, 2012)
Background Cardiovascular disease (CVD), is the primary cause of morbidity and mortality in patients with diabetes and have approximately - two to four times higher CVD rate than adult without diabetes. Low density lipoprotein cholesterol (LDL-C) is primarily used as the marker of cardiovascular risk in diabetes despite its several limitations. Although several newer markers of CVD are emerging, no marker has been established in Nepal. Objectives The study was designed to evaluate the non-high-density-lipoprotein- cholesterol(Non-HDL-C) and Total Cholesterol to High density lipoprotein cholesterol (TC:HDL-C ratio) as CVD risk marker in diabetes mellitus. Methods The study was conducted in the Department of Bbiochemistry, Kathmandu University School of Medical Sciences. The study comprised of 76 diabetic subjects and 60 non-diabetic subjects. The anthropometric and biochemical parameters were measured. The Non-HDL-C and TC:HDL-C ratio were also calculated employing their respective formula. Results Body mass index (BMI), waist circumference (WC), blood pressure and lipid parameters were significantly different between diabetic subjects and non-diabetic subjects. There was increased non-HDL-C and TC:HDL-C ratio in subjects with diabetes mellitus. Furthermore, statistically significant correlations of non-HDL-C and TC:HDL-C ratio were obtained with BMI, WC, total cholesterol, HDL-C and LDL-C in diabetic subjects. Conclusions The present study observation revealed that the Non-HDL-C and TC: HDL-C strongly correlate with established independent risk factors such as obesity(WC), elevated blood pressure, HDL-C and LDL-C in diabetes. Thus, the evaluation of Non-HDL-C and TC: HDL-C ratio can be used as the simple, cost-effective and cumulative marker of cardiovascular risk in diabetes mellitus. http://dx.doi.org/10.3126/kumj.v8i4.6239 Kathmandu Univ Med J 2010;8(4):398-404